IMPLEMENTATION OF BLOCKCHAIN TECHNOLOGY IN ACCOUNTING INFORMATION SYSTEMS: A SURVEY STUDY OF LOCAL GOVERNMENTS IN YOGYAKARTA - Nabila Salma Hanifah; Hafiez Sofyani (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study examines the adoption of Blockchain Technology in Accounting Information Systems (AIS) within local governments in Yogyakarta using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Specifically, it investigates the effects of performance expectancy, effort expectancy, social influence, and facilitating conditions, along with trust and regulatory support, on behavioral intention and actual usage. A quantitative survey was conducted among accounting and IT personnel in local government agencies, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that performance expectancy, trust, and regulatory support significantly and positively influence the intention to adopt blockchain-based AIS, while facilitating conditions are more closely associated with actual usage. Trust mediates the relationship between effort expectancy and intention, and regulatory support strengthens the effect of performance expectancy. The study contributes to the extension of the UTAUT model by incorporating trust and regulatory support in a public sector context, offering theoretical and practical implications for enhancing blockchain adoption. Findings suggest that improving system reliability, digital infrastructure, and regulatory clarity can increase the likelihood of successful implementation in local governments.